2021
DOI: 10.3390/su13020478
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Green Finance: A Survey of Literature in the Context of Green Bonds and Green Loans

Abstract: In response to the rapid development of green finance, this study evaluates a systematic literature survey with a focus on the determinants and the potential benefits of corporate engagement in environmentally responsible practices in the context of green bonds and green loans. We show that research has discovered that environmentally responsible practices not only enhance shareholder value but also the value accrued to nonfinancial stakeholders. Further, we provide an updated overview of research developments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(68 citation statements)
references
References 47 publications
0
64
0
4
Order By: Relevance
“…It analysed the publications on green finance, and their intellectual structure and networking. Gilchrist et al [7] concluded that environmentally responsible practices not only enhance shareholder value but also the value accrued to nonfinancial stakeholders. They provided an updated overview of research developments in relation to green bonds and syndicated loans.…”
Section: Research On Low-carbon and Sustainable Financingmentioning
confidence: 99%
“…It analysed the publications on green finance, and their intellectual structure and networking. Gilchrist et al [7] concluded that environmentally responsible practices not only enhance shareholder value but also the value accrued to nonfinancial stakeholders. They provided an updated overview of research developments in relation to green bonds and syndicated loans.…”
Section: Research On Low-carbon and Sustainable Financingmentioning
confidence: 99%
“…Also, these authors point to the need to develop policies that would discourage the non-fulfillment of obligations by green bond issuers. In this context, it is also necessary to pay attention to the study by Gilchrist et al (2021) who draw attention to the fact that the criteria for evaluating issuers of green bonds are vague, and therefore this reduces the interest of such issuers to follow specific rules of corporate greenness, and does not allow policymakers to assess the effectiveness of achieving the SDGs correctly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We identified a large topic about the main benefits of issuing green bonds. The advantages highlighted can be summarized as follows: (1) insurance against environmental risks; (2) a strong reputation and social trust; (3) lower cost of debt, pricing advantage; (4) diversification and a large investor base; (5) strong oversubscription; (6) pro-active messages to stakeholders; and (7) strengthened reputation (Bachelet et al 2019;Gilchrist et al 2021;CBI 2016;Wiśniewski and Zieliński 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Green finance has a different definition according to the priorities sets in developed and developing countries; for instance, coal finance is considered green in China while in Europe it is not (Gilchrist et al 2021). The European market has a leading role in terms of volume, followed by the Asia-Pacific and North American markets (Cheong and Choi 2020).…”
Section: Literature Reviewmentioning
confidence: 99%